2016
DOI: 10.15406/jaccoa.2016.04.00160
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Spinal Anesthesia

Abstract: In 1909 Thomas Jonnesco published his interesting paper under the title General spinal anesthesia through an approach of the subarachnoid space at a thoracic level, providing condition for surgery on the skull, head, neck and thorax. Etherington-Wilson proposed explaining the various possibilities for the spinal anesthesia. Leonardo da Vinci was considered the discoverer of Human and animal Anatomy. Image techniques have opened a gret new field for the study of anatomy in the living man. The modern means of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They found a greater space at the mid-thoracic level than the lumbar region, sufficient enough for intrathecal drugs 13 . Imbelloni et al investigated on magnetic resonance imaging of the thoracic spine and concluded that the maximum distance between the dura mater and the spinal cord is usually at the level of T5-T6 intervertebral space 12 . In this study, T5-T6 space was chosen because it has a maximum distance of 7.75 mm in comparison to other spaces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found a greater space at the mid-thoracic level than the lumbar region, sufficient enough for intrathecal drugs 13 . Imbelloni et al investigated on magnetic resonance imaging of the thoracic spine and concluded that the maximum distance between the dura mater and the spinal cord is usually at the level of T5-T6 intervertebral space 12 . In this study, T5-T6 space was chosen because it has a maximum distance of 7.75 mm in comparison to other spaces.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is significant debate regarding this practice around the world. The main concerns are fear of iatrogenic injury to the spinal cord, cephalad spread of local anaesthetic causing a complete block, and haemodynamic instability owing to blockade of cardio accelerator sympathetic fibres 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation